PEMENUHAN HAK PEKERJA PENYANDANG DISABILITAS BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI PT. MITRA DINAMIS SEJAHTERA KOTA BATAM - Syasha Mellya Karnain; Maria Maya Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
PT. Mitra Dinamis Sejahtera is one of the largest private companies in Batam City and isa specialist fire safety company providing fire faucets, fire alarms, emergency lifeboats and fireextinguishers. Regarding the labor quota that must be met by PT. Mitra Dinamis has employed 2people with disabilities, but there are several rights that have not been fulfilled. In Law Number13 of 2003 concerning Manpower Article 67 Paragraph (1) stipulates that employers who haveworkers with disabilities are required to provide protection according to the type and degree oftheir disability. This form of protection includes providing accessibility, providing work toolsand personal protective equipment. In an effort to protect, respect, promote and fulfill the rightsof persons with disabilities. In fact, the company has not provided protection such as theprovision of accessibility, hearing aids, special ladders for disabilities, and personal protectiveequipment.This research is a type of empirical research or sociological legal research. Sociologicallegal research is research that is carried out directly on location or in the field to obtain data toprovide a complete and clear picture of the problem under study. Data collection was carriedout using interviews, questionnaires and conducting literature studies using both books and datafrom the internet in the form of articles related to this writing.The author concludes that companies have not fully provided protection for workers withdisabilities. the company only provides protection in general and there are inhibiting factorssuch as internal companies, indecisiveness of Batam City Government, Lack of Knowledge, andBudget. Furthermore, the authors provide suggestions that the Government, companies andsociety must change the anti-discrimination stigma against persons with disabilities, byproviding motivation to do work like other workers. There needs to be cooperation between thegovernment and companies to carry out the fulfillment of special rights for workers withdisabilities. As well as the need for quality improvement in fulfilling the rights of workers withdisabilities, in addition to education and training, it can be carried out by giving directions fromcompany leaders or from the government. It is also necessary to improve the workingenvironment both within the company's internalKeywords: Fulfillment, Persons with Disabilities, Employment.